2009
DOI: 10.1051/0004-6361/200811461
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray eclipse of the dwarf nova HT Cassiopeiae observed by theXMM-Newton satellite: spectral and timing analysis

Abstract: Context.A cataclysmic variable is a binary system consisting of a white dwarf that accretes material from a secondary object via the Roche-lobe mechanism. In the case of long enough observation, a detailed temporal analysis can be performed, allowing the physical properties of the binary system to be determined. Aims. We present an XMM-Newton observation of the dwarf nova HT Cas acquired to resolve the binary system eclipses and constrain the origin of the X-rays observed. We also compare our results with prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…• ; see equation 1 of Nucita et al 2009; see also Wheatley & West 2003). This is ∼5 times the radius that can be expected for a 0.8 M WD, but considered the large uncertainties the value is consistent with the X-rays being emitted from the WD or close to it, and also with estimates of the inner radius of the truncated disc of a CV (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…• ; see equation 1 of Nucita et al 2009; see also Wheatley & West 2003). This is ∼5 times the radius that can be expected for a 0.8 M WD, but considered the large uncertainties the value is consistent with the X-rays being emitted from the WD or close to it, and also with estimates of the inner radius of the truncated disc of a CV (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…The measure of the ingress and egress allowed us to estimate the size of the X-ray emitting region. In doing this, we adopted a geometry similar to that describing the X-ray eclipse observed for the CV HT Cassiopea (see Nucita et al 2009) and, by using the orbital parameters given in Wood et al (1986), we find that the size of the X-ray source is 0.0119 R , which is comparable to the white dwarf radius (0.0125 R ).…”
Section: X-ray Temporal Analysis Resultsmentioning
confidence: 99%
“…X-ray eclipses have been observed by the XMM-Newton satellite in various CVs, including OY Car (Ramsay et al 2001; but see also Wheatley & West 2003, for a detailed study) and HT Cas (Nucita et al 2009). In both cases, it was possible to find that the X-ray emitting region (possibly a BL) has a size comparable with that of the central white dwarf, confirming the mass accretion scenario for a dwarf nova system.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the low count rate (and, hence, low signalto-noise ratio, S/N) and poor time sampling of the DW UMa X-ray light curve, it is difficult to make a meaningful comparison with the X-ray light curves of other CVs; for example, the flatbottomed total eclipses seen in the XMM-Newton observation of the dwarf novae HT Cas (Nucita et al 2009b) and OY Car (Ramsay et al 2001), or the partial X-ray eclipse observed with Suzaku in the dwarf nova V893 Sco (Mukai et al 2009). The best comparison might be made with the X-ray eclipse seen in XMMNewton observations of the longer-period (P orb = 4.72 hr) novalike CV UX UMa (Pratt et al 2004); however, we note that in the case of UX UMa, the eclipse is observed in only the hard X-ray light curve and not the soft, whereas the situation is reversed for DW UMa.…”
Section: X-ray and Optical Light Curvesmentioning
confidence: 99%
“…Nonetheless, of the historically well-known SW Sex stars, DW UMa had the highest RASS X-ray count rate (1.4 ± 0.2 ct s −1 compared to 0.004 ± 0.001 ct s −1 for WX Ari, 0.0062 ± 0.0006 ct s −1 for PX And, and non-detections for SW Sex, V1315 Aql, V1776 Cyg, BH Lyn, and V442 Oph), suggesting it as the most suitable target for future exploration in the X-ray regime. While approximately a dozen dwarf novae have been observed with XMM-Newton (e.g., see Pandel et al 2003Pandel et al , 2005Wheatley & West 2003;Hilton et al 2007;Nucita et al 2009b), only three novalike CVs have been observed: UX UMa (Pratt et al 2004), SDSS093214.82+495054.7 (Hilton et al 2009), and now DW UMa. Little is known about SDSS0932: it likely has a very long orbital period, in excess of 10 hr, and only an upper limit Xray flux of 0.014 ct s −1 from XMM-Newton.…”
Section: Introductionmentioning
confidence: 99%